If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4.8k + 6.4 = 8.48 Reorder the terms: 6.4 + -4.8k = 8.48 Solving 6.4 + -4.8k = 8.48 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6.4' to each side of the equation. 6.4 + -6.4 + -4.8k = 8.48 + -6.4 Combine like terms: 6.4 + -6.4 = 0.0 0.0 + -4.8k = 8.48 + -6.4 -4.8k = 8.48 + -6.4 Combine like terms: 8.48 + -6.4 = 2.08 -4.8k = 2.08 Divide each side by '-4.8'. k = -0.4333333333 Simplifying k = -0.4333333333
| p-49p=-7/9 | | Y-12=-4(x+10) | | 2x+11=3+4x-8 | | 9x(x-6)=(2x+1)(x-6) | | 5a^2+21a=20 | | y=-2x^2-40x-205 | | 3/4-12b=-3b | | 79x=-6380 | | 187-6x=13 | | 2x^2-48=-10x | | 5p^2=3p | | 6x+16x-12=180 | | y-4y=6 | | -4+8(x-5)=17x+6-9x | | y=x^2-3x+6x^3-5x+1 | | 6-8x-3=54+4x-15 | | (4x-18)=1 | | 7x-180= | | 5(k-4)-4(k+2)-13=-35 | | (6x+1)-180= | | 2r=.142 | | 3(x^2)-8x-16=0 | | 2x+4x=3+2 | | 3x+29=12x-7 | | 12x-24x^2-18=0 | | x=-654 | | 3x^2*y-5x*y+4y= | | -6(2w+1)-w=20 | | (3x+8)=(6x+1) | | 12x-24x-18=0 | | 3x^2+24x+5=y | | (6x+1)=(3x+8) |